Laparoscopic bladder diverticulectomy in a child with situs inversus totalis: A case report and literature review - Chen, Jitao; Liu, Fei; Tian, Jie; Xiang, Mingfeng (Frontiers in Surgery, 2022)
Situs inversus totalis（SIT）is a rare internal laterality disorders, which is characterized by the mirror arrangement of organs. Multiple gene mutations and maternal environmental factors are thought to have caused this variation. It is usually challenging to perform laparoscopic surgery in this case. Bladder diverticulum is uncommon in children with an incidence of 1.7%.We report a 14-year-old male patient who was admitted to our department because of lower abdominal pain and frequent urination. A series of examinations confirmed the rare combination of giant bladder diverticulum and SIT. After full preoperative discussion, we performed laparoscopic bladder diverticulectomy. The operation was successful. To the best of our knowledge this is the first report in the world. The article summarizes the technical key points and difficulties of performing this kind of operation. In addition, in the process of reviewing the literature, we found that SIT often coexisted with some high-risk factors of bladder diverticulum in some special syndromes. It is helpful to further understand and provide experience in diagnosis and treatment for the rare combination of bladder diverticulum and SIT in children.